2019
DOI: 10.3390/w11122605
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Wetting on the Tibetan Plateau during 1970–2017

Abstract: Based on daily observation records at 277 meteorological stations on the Tibetan Plateau (TP) and its surrounding areas during 1970–2017, drought evolution was investigated using the Standardized Precipitation Evapotranspiration Index (SPEI). First, the spatiotemporal changes in the growing season of SPEI (SPEIgs) were re-examined using the Mann–Kendall and Sen’s slope approach—the piecewise linear regression and intensity analysis approach. Then, the persistence of the SPEIgs trend was predicted by the Hurst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The MK is a non-parametric test that compares the presence of a trend in a time-series to the null hypothesis that there is no trend [102]. The WMO strongly recommends the MK test when examining meteorological and hydrological variables [102,103], and it has been widely used in environmental research for temporal trend analysis [102,104]. The significance of the trends was tested in this study at the α = 0.05 significance level.…”
Section: Trend Analysis Mann-kendall Test and Theil-sen Slope Estimatormentioning
confidence: 99%
“…The MK is a non-parametric test that compares the presence of a trend in a time-series to the null hypothesis that there is no trend [102]. The WMO strongly recommends the MK test when examining meteorological and hydrological variables [102,103], and it has been widely used in environmental research for temporal trend analysis [102,104]. The significance of the trends was tested in this study at the α = 0.05 significance level.…”
Section: Trend Analysis Mann-kendall Test and Theil-sen Slope Estimatormentioning
confidence: 99%
“…Wang et al considered that drought is caused by a decrease in precipitation and an increase in temperature [39]. Some scholars have also found that the TP has experienced a continuous wet trend since the 1950s [40][41][42][43][44]. The prolonged rainy season and increased precipitation can effectively alleviate drought in the region [41,43].…”
Section: Introductionmentioning
confidence: 99%
“…Frontiers in Environmental Science frontiersin.org degree of drought trended to ease, and the evolution of drought had noticeable interdecadal differences after 1997 (Liang et al, 2018). During the growth season, though the northeastern and southern parts experienced a significant wetting trend, the eastern fringe of the QTP tended to be dry, and this trend will continue (Zhang et al, 2019). The altitude dependence of drought characteristics was investigated based on SPEI and 4,000 m a. s. l was determined as the dividing line, the higher the altitude, the greater the changing trend (Feng et al, 2020).…”
Section: Figurementioning
confidence: 99%